Three Dimensional-Arterial Spin Labeling Evaluation of Improved Cerebral Perfusion After Limb Remote Ischemic Preconditioning in a Rat Model of Focal Ischemic Stroke - Zheng, Tianxiu; Lai, Xiaolan; Lu, Jiaojiao; Chen, Qiuyan; Wei, Dingtai (Frontiers in Neuroanatomy, 2022)
Purpose: To investigate the application value of 3D-ASL for evaluating distal limb ischemic preconditioning to improve acute ischemic stroke perfusion. Methods: A total of 40 acute ischemic stroke (AIS) patients treated in our hospital from January 2020 to December 2020 were recruited, and 15 healthy individuals who were examined in our hospital during the same period were included as the control group; all of these participants were scored on the National Institutes of Health Stroke Scale (NIHSS) and examined by MRI. Sequences included conventional sequences, diffusion-weighted imaging (DWI), magnetic resonance angiography (MRA) and 3D arterial spin labeling (3D-ASL). After 3 months of treatment, AIS patients were scored on the modified Rankin Scale (mRS). Fifty-five adult male Sprague-Dawley rats were randomly divided into three groups: twenty the middle cerebral artery occlusion (MCAO) group, twenty the MCAO + limb remote ischemic preconditioning (LRP) group and 15 sham group. Forty-eight hours after the procedures, conventional MRI, DWI and 3D-ASL sequence data were collected, and TTC staining and behavioral scoring were performed. CBF values was recorded in the infarct lesion area and the corresponding contralateral area. The pathological changes in brain tissues were observed by HE staining, and the expression of vascular endothelial growth factor (VEGF) and platelet endothelial cell adhesion molecule-1 (PECAM-1/CD31) in brain tissues was detected by immunofluorescence and real-time quantitative polymerase chain reaction (RT–qPCR). The protein expression of VEGF was detected by Western blotting. Results: The CBF values in the infarct area of AIS patients were significantly lower than the corresponding areas on the contralateral side, and the CBF values had a high specificity and sensitivity for prognosis. LRP significantly reduces the infarct area, improves behavioral deficits in rats with cerebral ischemia, reduces neurological injury and histological damage, protects vascular structures, and promotes neovascularization. In addition, 3D-ASL showed a significant increase in brain tissue perfusion in the ischemic area after LRP, and the expression of VEGF and CD31 showed a significant positive correlation with CBF values. Conclusion: 3D-ASL can be used to evaluate LRP to improve stroke perfusion, and its protective effect may be closely related to LRP-induced vascular regeneration.